Neural signal propagation atlas of Caenorhabditis elegans - Randi, Francesco; Sharma, Anuj K.; Dvali, Sophie; Leifer, Andrew M. (Nature (London), 2023)
Establishing how neural function emerges from network properties is a fundamental problem in neuroscience 1 . Here, to better understand the relationship between the structure and the function of a nervous system, we systematically measure signal propagation in 23,433 pairs of neurons across the head of the nematode Caenorhabditis elegans by direct optogenetic activation and simultaneous whole-brain calcium imaging. We measure the sign (excitatory or inhibitory), strength, temporal properties and causal direction of signal propagation between these neurons to create a functional atlas. We find that signal propagation differs from model predictions that are based on anatomy. Using mutants, we show that extrasynaptic signalling not visible from anatomy contributes to this difference. We identify many instances of dense-core-vesicle-dependent signalling, including on timescales of less than a second, that evoke acute calcium transients—often where no direct wired connection exists but where relevant neuropeptides and receptors are expressed. We propose that, in such cases, extrasynaptically released neuropeptides serve a similar function to that of classical neurotransmitters. Finally, our measured signal propagation atlas better predicts the neural dynamics of spontaneous activity than do models based on anatomy. We conclude that both synaptic and extrasynaptic signalling drive neural dynamics on short timescales, and that measurements of evoked signal propagation are crucial for interpreting neural function. Measurements of signal propagation in more than 23,000 pairs of neurons from nematode worms show that predictions of neural function made on the basis of anatomy are often incorrect, in part owing to the effects of extrasynaptic signalling.